PERAN PENDIDIKAN ANTI KORUPSI DALAM MEMBANGUN BUDAYA POLITIK DEMOKRATIS DI KALANGAN MAHASISWA - Serlin Fitriana; Naysya Desky; Novita Sary Hasibuan; Sapta Kesuma; Muharri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Corruption is one of the fundamental problems that hinder democratic development in Indonesia. This study aims to examine the role of anti-corruption education in building a democratic political culture among university students. Using a descriptive qualitative approach and literature study, this research analyzes how the internalization of anti-corruption values such as honesty, integrity, responsibility, and transparency can encourage the formation of democratic student character. The results show that anti-corruption education significantly contributes to shaping students' political awareness, increasing democratic participation, and strengthening commitment to good governance values. The implementation of anti-corruption education through formal curricula, extracurricular activities, and campus culture has proven effective in transforming students into agents of change with integrity.